The body, cast(out) of utopia. A commentary on The Automaton, by Xavier Abril (Anclajes, 2018)
Xavier Abril’s avant-garde nouvelle, The Automaton (1931), exhibits a distancing from the Peruvian indigenous narrative. In this regard, based on analysis of its most groundbreaking techniques, such as montage and fragmentation, or even through a review of paratexts prior to publication, one notices a challenge to both the concept of novel as well as that of subject. The latter is redefined by means of its conceptualization as automaton, a fundamental piece of a capitalist socioeconomic structure, and consequently its corresponding narrative form, the novel, whose characterization becomes a vehicle of said criticism.
Keywords: Xavier Abril; Peruvian literature; literary criticism; twentieth century; Perú